Prospects for top-down derivation - Jan-Wouter Zwart (Universitat Autònoma de Barcelona, 2009)
This article explores a model of grammar involving top-down derivations, where each step (“splitmerge”) yields an asymmetric pair of elements relevant to the expression of order, information, and grammatical features. These derivations are inevitably layered, in the sense that the output of a previous derivation may appear as an atom in the numeration for the next derivation. It is suggested that opacity effects follow from the layering of derivations, not from conditions on movement. While the main questions surrounding the model contemplated here involve the ‘when’ and ‘what’ of merge, this article focuses on the more preliminary question of the ‘how’ of merge.